Sobrecarga del cuidador primario del adulto mayor y su relación con su funcionamiento familiar - Sánchez González, Daniel (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Introduction Life expectancy is increasing and with it the aging of the population, parallel to this phenomenon the increase in non-communicable diseases that cause dependence in the elderly, where the caregiver plays an indispensable role of responsibility, the same factor can cause conditions in their own health and in family dynamics Objective To analyze the perception of the level of burden experienced by the primary caregiver of the dependent older adult. Methodology Quantitative, correlational, cross-sectional and non-experimental study, in 6 communities of the municipality of San Felipe del Progreso, State of Mexico, of 60 primary caregivers with their respective older adult, with convenience sampling. The Zarit instruments were used with an α=.89 and the family Apgar with α= .96. The ethical guidelines in research were complied with and the anonymity and confidentiality of the data was maintained. The statistical analysis was with SPSS version 27. Results The majority of the caregivers were women with a mean age of 50.9 (SD=10.2) dedicated to household activities, being daughters of the older adult in addition to having more than 5 years of care, for the older adult the female gender predominated. With a mean age of 83.9 (SD=5.4), their health problems include physical conditions and noncommunicable diseases such as Diabetes mellitus 2 and high blood pressure. Regarding the perception of the level of burden experienced by the primary caregiver, it was intense overload with good family functioning. Conclusions Caregivers reported greater overload the longer they cared, reporting good family dynamics in all cases.

Introducción La esperanza de vida va en aumento y con ella el envejecimiento de la población, paralelamente a este fenómeno el aumento de enfermedades no transmisibles que causan dependencia de la persona adulta mayor, donde el cuidador juega un papel indispensable de responsabilidad, mismo factor puede causar afecciones en su propia salud y en la dinámica familiar Objetivo Analizar la percepción del nivel de carga que experimenta el cuidador primario del adulto mayor dependiente. Metodología Estudio cuantitativo, correlacional, transversal y no experimental, en 6 del municipio de San Felipe del Progreso, Estado de México, a 60 cuidadores primarios con su respectivo adulto mayor, con un muestreo a conveniencia. Se utilizaron los instrumentos de Zarit con un α=.89 y el Apgar familiar con α= .96, Se cumplieron las pautas éticas en investigación y se guardó el anonimato y la confidencialidad de los datos, el análisis estadístico fue con el SPSS versión 27. Resultados La mayoría de los cuidadores fueron mujeres con una edad media de 50.9 (DE=10.2) dedicadas a las actividades del hogar, siendo hijas del adulto mayor además de tener más de 5 años de cuidado, para el adulto mayor predomino el género femenino con una edad media de 83.9 (DE=5.4) en sus problemas de salud destaco las afecciones físicas y las enfermedades no trasmisibles como la Diabetes mellitus 2 y la hipertensión arterial. Respecto a la percepción del nivel de carga que experimenta el cuidador primario fue de sobrecarga intensa con un buen funcionamiento familiar. Conclusiones Los cuidadores reportaron mayor sobrecarga a mayor tiempo de cuidado reportando en todos los casos buena la dinámica familiar.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2024-1554; Gestión, dirección y liderazgo; Agotamiento; Cuidador primario; Sobrecarga; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18924